Nkanelo wa ku oviwa ka tinfanelo ta vavasati eka tsalwa ra Khale ka Makwangala hi F. Rikhotso - Lamula, Allettah Tintswalo (University of Limpopo, 2013)
The main aim of this study is to examine women’s abuse with special reference to Xitsonga folklore, Khale ka Makwangala by F. Rikhotso. This study also shows characters who are abused and those who cause this abuse. The first chapter reveals the general outline of the study, the problem statement, the aim, the importance and its methodology. The most important terms of the study have been explained in this chapter so as to reveal what is expected to be analyzed. Some of the definitions of the Constitution have been given. Chapter two gives short summary of the folklore Khale ka Makwangala by F. Rikhotso which has been examined together with the history of their authors. The definitions of the word human rights have been included and defined in this chapter. In this chapter, other folklores which have been selected for analysis have been analysed. Chapter three explains, defines and analyses the themes of selected folklores. The definitions of themes have been given in this chapter. These definitions make it easier to understand what themes are. Chapter four deals with the general summary of this mini-dissertation. The recommendations and findings for further research have been indicated in this chapter.
Analysis of the abuse of women's rights in Xitsonga folklore khale kha Magwangala F. Rikhotso
Thesis (M.A. (African Languages)) -- University of Limpopo, 2013
Keywords: Abuse; folklore; 896.3978; Tsonga literature; Abused women in literature; African literature - History and criticism